Profile of Bottom Soil of Yellow Podzolic Red (YPR) with Different Ages in The Catfish (Pangasius sp.) Intensive culture - Yunus, Ahmad; Hasibuan, Saberina; Syafriadiman, Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted from March to May 2017in the Koto Masjid Village, Kampar, Riau and observation parameters has done in the Environmental Quality Laboratory of Aquaculture Faculty of Fisheries and Marine University of Riau. The aim of research was to knowing the layers on the profile of bottom soil of yellow podzolic red (YPR) pond and its characteristic with different age which catfish cultivated (Pangasius sp.) intensively. This research used eksperiment method and had direct observation with 1 factor, 4 treatments and 3 replications. The highest basal soil profile of the initial layer of flocculent layer (F) was P1 (0-5 years age) of 0.98 cm while in F final was P3 (age of 11-15 years). Furthermore, in the highest mixed sediment layer (S) layer, P3 is 3.98 cm, whereas in the final S layer is P2 (aged pond 6-10 years) that is 7.91 cm. Furthermore, the highest stable matures is stable sediment (M) is P4 (16-20 years age pond) which is 8.59 cm, while in the final M layer is P2 which is 11,50 cm. The next stage of the highest transitional layer (T) layer is P3 which is 10.54 cm, whereas in the final T layer it is P2 that is 17.16 cm. The measured soil quality parameters are still considered good. Soil sand fraction 74,16-89,66%, silt fraction 2,66-9,83%, clay fraction 7,66-16,00%. Ground BV 0.45-1.58 g / cm3, ground BJ 1,53-2,18 g / ml, soil porosity 14,75-66,26%, C organic soil 1,97-5,60% and pH 6,80-6,96.Keywords: Bottom Soil Pond Profile, Flocculent layer, YellowPodsolik Red, Pangasius sp.